PROBLEMS OF ECOLOGICALLY SAFE LAND USE IN MODERN CONDITIONS - Kupriyanchyk, I. P. (Землеустрій, кадастр і моніторинг земель, 2012)
The problems of ecologicall safe use of the land resources. In particular, the essence of ecologically safe use of the land resources, the main objectives and strategy.